Exosite 1 thrombin inhibition with JNJ-64179375 inhibits thrombus formation in a human translational model of thrombosis. Issue 3 (26th October 2018) - Wilson, Simon J; Connolly, Thomas M; Peters, Gary; Ghosh, Atalanta; Johnson, Maureen; Newby, David E
Abstract: Aims: JNJ-64179375 (hereafter JNJ-9375) is a first-in-class, highly specific, large molecule, exosite 1 thrombin inhibitor. In preclinical studies, JNJ-9375 demonstrated robust antithrombotic protection with a wider therapeutic index when compared to apixaban. The purpose of the present study was to examine for the first time the antiplatelet, anticoagulant and antithrombotic effects of JNJ-9375 in a translational model of ex vivo human thrombosis. Methods and results: Fifteen healthy volunteers participated in a double-blind randomized crossover study of JNJ-9375 (2.5, 25, and 250 μg/mL), bivalirudin (6 μg/mL; positive control), and matched placebo. Coagulation, platelet activation, and thrombus formation were determined using coagulation assays, flow cytometry, and an ex vivo perfusion chamber, respectively. JNJ-9375 caused concentration-dependent prolongation of all measures of blood coagulation (prothrombin time, activated partial thromboplastin time, and thrombin time; P  < 0.001 for all) and agonist selective inhibition of thrombin (0.1 U/mL) stimulated platelet p-selectin expression ( P  < 0.001) and platelet-monocyte aggregates ( P  = 0.002). Compared to placebo, JNJ-9375 (250 μg/mL) reduced mean total thrombus area by 41.1% (95% confidence intervals 22.3 to 55.3%; P  < 0.001) at low shear and 32.3% (4.9 to 51.8%; P  = 0.025) at high shear. Under both shear conditions, there was a dose-dependent decrease in fibrin-rich thrombus ( P  < 0.001 for both) but not platelet-rich thrombus ( P  = ns for both). Conclusion: Exosite 1 inhibition with JNJ-9375 caused prolongation of blood coagulation, selective inhibition of thrombin-mediated platelet activation, and reductions in ex vivo thrombosis driven by a decrease in fibrin-rich thrombus formation. JNJ-9375 represents a novel class of anticoagulant with potential therapeutic applications.